Multi‐Parametric Evaluation of Cerebral Hemodynamics in Neonatal Piglets Using Non‐Contrast‐Enhanced Magnetic Resonance Imaging Methods. Issue 4 (6th May 2021) - Liu, Dapeng; Jiang, Dengrong; Tekes, Aylin; Kulikowicz, Ewa; Martin, Lee J.; Lee, Jennifer K.; Liu, Peiying; Qin, Qin
Abstract : Background: Disruption of brain oxygen delivery and consumption after hypoxic–ischemic injury contributes to neonatal mortality and neurological impairment. Measuring cerebral hemodynamic parameters, including cerebral blood flow (CBF), oxygen extraction fraction (OEF), and cerebral metabolic rate of oxygen (CMRO2 ), is clinically important. Purpose: Phase‐contrast (PC), velocity‐selective arterial spin labeling (VSASL), and T2 ‐relaxation‐under‐phase‐contrast (TRUPC) are magnetic resonance imaging (MRI) techniques that have shown promising results in assessing cerebral hemodynamics in humans. We aimed to test their feasibility in quantifying CBF, OEF, and CMRO2 in piglets. Study Type: Prospective. Animal Model: Ten neonatal piglets subacutely recovered from global hypoxia‐ischemia ( N = 2), excitotoxic brain injury ( N = 6), or sham procedure ( N = 2). Field Strength/Sequence: VSASL, TRUPC, and PC MRI acquired at 3.0 T. Assessment: Regional CBF was measured by VSASL. Global CBF was quantified by both PC and VSASL. TRUPC assessed OEF at the superior sagittal sinus (SSS) and internal cerebral veins (ICVs). CMRO2 was calculated from global CBF and SSS‐derived OEF. End‐tidal carbon dioxide (EtCO2 ) levels of the piglets were also measured. Brain damage was assessed in tissue sections postmortem by counting damaged neurons. Statistical Tests: Spearman correlations were performed to evaluate associations among CBF (by PC or VSASL), OEF, CMRO2, EtCO2, and the pathological neuron counts. Paired t ‐test was used to compare OEF at SSS with OEF at ICV. Results: Global CBF was 32.1 ± 14.9 mL/100 g/minute and 30.9 ± 8.3 mL/100 g/minute for PC and VSASL, respectively, showing a significant correlation ( r = 0.82, P < 0.05). OEF was 54.9 ± 8.8% at SSS and 46.1 ± 5.6% at ICV, showing a significant difference ( P < 0.05). Global CMRO2 was 79.1 ± 26.2 μmol/100 g/minute and 77.2 ± 12.2 μmol/100 g/minute using PC and VSASL‐derived CBF, respectively. EtCO2 correlated positively with PC‐based CBF ( r = 0.81, P < 0.05) but negatively with OEF at SSS ( r = −0.84, P < 0.05). Relative CBF of subcortical brain regions and OEF at ICV did not significantly correlate, respectively, with the ratios of degenerating‐to‐total neurons ( P = 0.30, P = 0.10). Data Conclusion: Non‐contrast MRI can quantify cerebral hemodynamic parameters in normal and brain‐injured neonatal piglets. Level of Evidence: 1 Technical Efficacy Stage: 2